The potency of green education-based blended learning in biology students at the Hindu University of Indonesia - I Made Dwi Mertha Adnyana; Ni Luh Gede Sudaryati (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2022)
The impact of the COVID-19 pandemic on the field of education has resulted in a decrease in interest in studying biology students and a lack of concern for the surrounding environment. This study aims to determine the potential of a blended learning model based on green education for biology students at the Hindu University of Indonesia. The research method of systematic literature review uses 20 reputable journals and 24 supporting journals. The study was conducted for two months. A human instrument is used in this research in collecting, reviewing, and analyzing data. Determination of the sample using purposive sampling. Data analysis using meta-synthesis. The results of the meta-synthesis of the potential of blended learning in universities are based on research objectives: 50% to test the effect or effectiveness; 30% of research methods use R&D (Research & Development); 30% of data collection techniques use tests and questionnaires, and 30% of data analysis uses analysis descriptive. The potential implementation of the green education-based blended learning model has three main criteria and pillars, namely: 1) flexibility and ease of accessibility; 2) Alignment, enhancement, and enhancement of environmental quality; and 3) increasing student independence in the learning process. The green education-based blended learning model can be applied because it helps train students' skills in developing problem-based science, improving critical thinking skills, analyzing problems and making decisions quickly and objectively in providing solutions to problems in the surrounding environment.Abstrak Dampak pandemi COVID-19  di bidang pendidikan mengakibatkan penurunan minat belajar mahasiswa biologi serta kurangnya kepedulian terhadap lingkungan sekitar. Penelitian ini bertujuan untuk mengetahui potensi model blanded learning berbasis green education pada mahasiswa biologi  Universitas Hindu Indonesia. Metode penelitian Systematic Literature Review menggunakan 20 jurnal bereputasi dan 24 jurnal pendukung. Penelitian dilakukan selama 2 bulan.  Human Instrument digunakan dalam penelitian ini dalam mengumpulkan, mengkaji dan menganalisis data. Penentuan sampel menggunakan purposive sampling. Analisis data menggunakan meta-sintesis. Hasil meta-sintesis potensi blended learning di perguruan tinggi berdasarkan tujuan penelitian, 50% untuk menguji pengaruh atau efektivitas, metode penelitian 30% menggunakan R&D (Research & Development), teknik pengumpulan data 30% menggunakan tes dan angket dan analisis data 30% menggunakan analisis deskriptif. Potensi implementasi model blended learning berbasis green education memiliki tiga kriteria dan pilar utama, yakni: 1) Fleksibilitas dan kemudahan aksesibilitas 2) Penyelarasan, perbaikan dan peningkatan kualitas lingkungan, dan 3) meningkatkan kemandirian peserta didik dalam proses pembelajaran. Model blended learning berbasis green education berpotensi diterapkan karena bermanfaat untuk melatih keterampilan peserta didik dalam mengembangkan sains berbasis masalah, meningkatkan keterampilan berpikir kritis, menganalisis masalah dan mengambil keputusan secara cepat dan objektif dalam memberikan solusi terhadap permasalahan di lingkungan sekitar.